Pemberdayaan Ekonomi Eks-ODGJ Melalui Farming Daily Activities - Sari, Novita Erliana (Amalee: Indonesian Journal of Community Research and Engagement, 2022)
Abstrak: Orang dengan gangguan jiwa atau biasa disebut sebagai ODGJ adalah istilah yang dipakai untuk orang yang mengalami gangguan kesehatan mental. Doho adalah salah satu Desa di Kecamatan Dolopo Kabupaten Madiun dengan jumlah ODGJ yang relatif besar. Jumlah ODGJ di desa tersebut sebanyak 27 orang. ODGJ di Desa Doho memperoleh diskriminasi baik dari anggota keluarga maupun masyarakat sekitar. Kurangnya pemahaman membuat masyarakat menganggap bahwa ODGJ tidak dapat diberdayakan sehingga tidak diberikan kesempatan untuk hidup layak manusia meskipun kondisinya dinyatakan stabil (eks-ODGJ). Kegiatan pertanian sehari-hari dipilih sebagai sarana untuk memberdayakan eks- ODGJ ekonomi. Adapun uraian kegiatan yang akan dilaksanakan adalah: (1) Survei awal (2) Identifikasi masalah (3) Analisis kebutuhan (4) Penetapan target sasaran (5) Pelaksanaan (6) Pemantauan dan Evaluasi. Hasil yang dicapai setelah penerapan program farming daily activities yaitu munculnya rasa tanggung jawab eks-ODGJ untuk menyelesaikan seluruh tanggung jawab harian untuk merawat hewan ternak hingga siap untuk dipanen dan dipasarkan, selain itu kondisi jiwa eks-ODGJ relatif stabil. Abstract: People with mental disorders, commonly called ODGJ, are a term for people who experience mental health disorders. This community service activity was motivated by the large number of people in Doho Village, Dolopo District, Madiun Regency who experienced mental disorders (27 people) with mild, moderate, and severe conditions who still received discrimination and negative stigma both from their families and from the local community because they were considered no longer able to live everyday life. And productive. These Daily Farming Activities aim to empower the economy of ex-ODGJ so that they can return to living productively like humans in general. The sequence of activities carried out in this community service activity is as follows: (1) initial survey at the location of the activity, namely Doho Village, Dolopo District, Madiun Regency; (2) identify problems; (3) conduct a needs analysis of partners; (4) determine the target audience for community service; (5) implementation of community service activities; (6) monitoring and evaluation. The results that can be achieved after the farming daily activities program are the emergence of a sense of responsibility for ex-ODGJ to care for livestock until they are ready to be harvested and marketed. During the day-to-day farming activities service program, ex-ODGJ was relatively stable. This activity has a positive impact on rebuilding the productivity of ODGJ.